Pengembangan Video Pembelajaran Animasi Berbasis CTL Materi Siklus Mahkluk Hidup untuk Kelas IV - MAILAN, POPI (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
The aim of this research is to develop CTL-based animated learning video media on the Cycles of Living Creatures for class IV students. The research subjects were 15 students and 1 class IV teacher at SDN 23 Central Bengkulu. Meanwhile, the object is a CTL-based animated learning video. This research uses the development of the Borg and Gall model which was carried out to produce a learning product. These stages include the potential and problem stages, data collection, product design, design validation, design revision, limited experimentation, product revision, field trials, product revision, and mass product. However, development was carried out only up to stage seven (development). The instruments used were expert validation sheets and interview guidelines as well as practicality test questionnaires. The results of the research show that the CTL-based animated learning video media developed is very feasible and practical for use by class IV students and teachers in science learning, especially material on the Cycles of Living Creatures.